The impact of online shopping features on consumer buying behavior: A systematic literature review - Syamsuri, Abd. Rasyid; Arohman, Rifki; Halim, Abd.; Surbakti, Afridayanti; Saputra, Muhammad Renaldy (MID Publisher International, 2025)
This study examines the impact of online shopping features on consumer buying behavior by synthesizing findings from recent scholarly works through a systematic literature review. The research aims to identify how various digital features, including personalization, security mechanisms, interactive technologies, and social commerce elements, influence consumer trust, decision-making, and purchase intentions. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a structured selection process was applied to peer-reviewed journal articles, academic reports, and books published within the last five years, resulting in 25 studies included in the final review. A descriptive synthesis approach was used to categorize themes and compare patterns across different contexts. The findings indicate that functional aspects such as website design and usability strongly affect satisfaction and trust, while interactive and experiential features, including augmented reality, chatbots, and live streaming commerce, enhance engagement and drive purchasing outcomes. Additionally, the review highlights challenges related to privacy concerns, consumer fatigue, and ethical issues, suggesting that sustainable e-commerce strategies require balancing technological innovation with consumer-centric design. The study implies that platforms integrating trust, convenience, and personalization are more likely to achieve long-term consumer loyalty and competitive advantage in digital markets.